2014
DOI: 10.1063/1.4896077
|View full text |Cite
|
Sign up to set email alerts
|

Metallic 1T phase source/drain electrodes for field effect transistors from chemical vapor deposited MoS2

Abstract: Two dimensional transition metal dichalcogenides (2D TMDs) offer promise as opto-electronic materials due to their direct band gap and reasonably good mobility values. However, most metals form high resistance contacts on semiconducting TMDs such as MoS2. The large contact resistance limits the performance of devices. Unlike bulk materials, low contact resistance cannot be stably achieved in 2D materials by doping. Here we build on our previous work in which we demonstrated that it is possible to achieve low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
152
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(159 citation statements)
references
References 32 publications
4
152
0
3
Order By: Relevance
“…However, the emergence of single-layer MoS 2 [23] has attracted substantial research interest, which exhibits superior electrical and optical properties as a semiconducting TMD. Unlike graphene, silicene and germanane, monolayer MoS 2 does not suffer from a vanishing gap [23,24], and has been used to fabricate FETs [15,[25][26][27]. However, the band gaps of most explored 2D materials are smaller than 2.0 eV, which has greatly encumbered the development of 2D semiconductor based optoelectronic devices with response to photons with wavelengths of less than 620 nm, such as ultraviolet (UV)-and blue-light photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the emergence of single-layer MoS 2 [23] has attracted substantial research interest, which exhibits superior electrical and optical properties as a semiconducting TMD. Unlike graphene, silicene and germanane, monolayer MoS 2 does not suffer from a vanishing gap [23,24], and has been used to fabricate FETs [15,[25][26][27]. However, the band gaps of most explored 2D materials are smaller than 2.0 eV, which has greatly encumbered the development of 2D semiconductor based optoelectronic devices with response to photons with wavelengths of less than 620 nm, such as ultraviolet (UV)-and blue-light photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…23 Regarding electrode materials, Au is the most commonly chosen material and is widely adopted for metal electrodes because of its chemical stability and the good contact it can achieve with two-dimensional materials. 24,25 However, according to a recent report, 26 Ag, which exhibits a smooth surface and excellent wettability on MoS 2 , has also been proven to form good metal contacts and may help to boost the electronic performance of MoS 2 devices. Although considerable work has been done to study both types of metal contacts, produced by fabrication techniques based on thermal evaporation or electron beam evaporation, 27,28 research on Au or Ag electrodes produced via OIE is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…By using the 1T phase MoS 2 electrodes and well controlled phase interface, the contact resistance of 2H MoS 2 can be significant reduced without the performance loss. 16,17 Former studies suggested that the grain boundaries of the 2H monolayer MoS 2 have important effects on the electronic, magnetic and transport properties. [24][25][26][27] Similar with that of grain boundaries, the 1T/2H phase interface are supposed to be connected with many physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…15 This kind of bi-phase hybrid systems with semiconducting and metallic regions paved the way to design the new generation 2D photoelectric devices based on the in-plane metal/semiconductor heterostructures. 16,17 Compared with the comprehensive studies on the fabrications [18][19][20][21] and applications 22,23 of graphene/h-BN heterostructures, few reports focused on the in-plane 1T/2H MoS2 hybrid systems. [14][15][16] By using lithium based chemical exfoliation method, Eda et al 15 firstly synthetized a single layer of exfoliated MoS 2 consisting of both 2H and 1T phases then form chemically homogeneous atomic and electronic heterostructures with potential for novel molecular functionalities.…”
Section: Introductionmentioning
confidence: 99%